Crystal structure of {μ-6,6′-dimethoxy-2,2′-[ethane-1,2-diylbis(nitrilomethanylylidene)]diphenolato}(methanol)(nitrato)nickel(II)sodium - Olesia V. Moroz; Viktor A. Trush; Tatiana Yu. Sliva; Irina S. Konovalova; Vladimir M. Amirkhanov (Acta Crystallographica Section E, 2014)
In the molecular structure of the title compound, [NaNi(C18H18N2O4)(NO3)(CH3OH)], the Ni2+ ion has a slightly distorted square-planar coordination environment defined by two N and two O atoms which belong to a Schiff base ligand, viz. 6,6′-dimethoxy-2,2′-[ethane-1,2-diylbis(nitrilomethanylylidene)]diphenolate. Seven O atoms form the coordination environment of the Na+ ion: four from the Schiff base ligand, two from a bidentate chelating nitrate anion and one O atom from a coordinating methanol molecule. In the crystal, the bimetallic complexes are assembled into chains along the b-axis direction via weak C—H...O hydrogen-bond interactions. Neighbouring chains are in turn connected through bifurcated O—H...O hydrogen bonds that involve the coordinating methanol molecules and the nitrate anions, and through π–π stacking interactions between phenyl rings of neighbouring molecules.